2013
DOI: 10.1016/j.neuron.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Control of Synaptic Vesicle Replenishment and Short-Term Plasticity by Ca2+-Calmodulin-Munc13-1 Signaling

Abstract: Short-term synaptic plasticity, the dynamic alteration of synaptic strength during high-frequency activity, is a fundamental characteristic of all synapses. At the calyx of Held, repetitive activity eventually results in short-term synaptic depression, which is in part due to the gradual exhaustion of releasable synaptic vesicles. This is counterbalanced by Ca(2+)-dependent vesicle replenishment, but the molecular mechanisms of this replenishment are largely unknown. We studied calyces of Held in knockin mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(172 citation statements)
references
References 71 publications
12
154
0
2
Order By: Relevance
“…Sample eEPSC trains are shown in Figure 6A. Consistent with previous reports, eEPSC trains of wt calyx synapses showed mostly depression (Erazo-Fischer et al, 2007;Lipstein et al, 2013). In contrast, eEPSCs of Cplx1 Ϫ/Ϫ calyx synapses (n ϭ 50, P16 -P21) initially strongly facilitated.…”
Section: Comparison Of Short-term Plasticity In Calyx Synapses Of Cplx1supporting
confidence: 88%
“…Sample eEPSC trains are shown in Figure 6A. Consistent with previous reports, eEPSC trains of wt calyx synapses showed mostly depression (Erazo-Fischer et al, 2007;Lipstein et al, 2013). In contrast, eEPSCs of Cplx1 Ϫ/Ϫ calyx synapses (n ϭ 50, P16 -P21) initially strongly facilitated.…”
Section: Comparison Of Short-term Plasticity In Calyx Synapses Of Cplx1supporting
confidence: 88%
“…Alternatively, a conformational change within Munc13s, induced by the modulators, may underlie superpriming. This possibility is supported by recent studies, which show that mutations in the regulatory domains of Munc13-1 enhance the baseline release probability of SVs (9,21).…”
Section: Discussionmentioning
confidence: 54%
“…Similar to CaM inhibitors, perturbations of proteins involved in endocytosis have a specific effect on CDR, implying that CaM-dependent CDR is closely related to clearing refractory release sites (22). Recently, a knock-in mouse line was established that harbors a CaM-insensitive mutant of Munc13-1 (21). It was shown that recovery of the FRP after prolonged depolarization is slowed down in calyces of such mice, mimicking block of CDR.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the calyx of Held where CaM appears to act via Munc13 to enhance vesicle priming at the membrane (Z. Lipstein et al, 2013), our results suggest that CaM acts on ribbon-associated proteins to increase the likelihood that vesicles attach to ribbons. Furthermore, by disrupting CaM, we found that Ca 2+ -dependent replenishment accelerates replenishment in cones over short time intervals and thus plays an important role in setting the high-frequency fall off of cone synaptic transmission.…”
Section: Patch-clamp Electrophysiologymentioning
confidence: 63%